Enhancing ESP Motivation and Proficiency Through CALL: A Quasi-Experimental Study with Islamic Banking Students - Reza Anggriyashati Adara; Purnama Putra (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
Computer-Assisted Language Learning (CALL) has been widely implemented to support motivation and language development in English for Specific Purposes (ESP) instruction. However, empirical studies examining its use in English for Islamic Banking within Islamic higher education contexts remain limited. This study investigates the effectiveness of CALL in enhancing students’ motivation and language skills in an English for Islamic Banking course at an Islamic higher education institution. Employing a quasi-experimental one-group pre-test/post-test design, the study involved 20 undergraduate Islamic Banking students who participated in a CALL-based instructional intervention conducted over six sessions. Data were collected through language proficiency assessments based on an IELTS speaking rubric and a motivation questionnaire based on Keller’s ARCS model. The findings indicate a statistically significant improvement in language proficiency (t(19) = 2.42, p = 0.025, Cohen’s d = 0.53). In addition, Attention (d = 0.63), Confidence (t(19) = 2.29, p = 0.033, d = 0.52), and Satisfaction (d = 1.17) showed significant gains, with Satisfaction demonstrating the largest effect size. Meanwhile, the Relevance component showed no significant change (p = 0.33), possibly due to students’ prior perception of the course content as inherently applicable to their academic and professional goals. The study suggests that CALL can serve as an effective pedagogical approach for supporting learner motivation and language development in ESP courses within Islamic higher education, particularly when instructional activities are aligned with learners’ professional contexts in Islamic finance.